PEMBUATAN MODUL ELEKTRONIK (E-MODUL) SEBAGAI SOLUSI PEMBELAJARAN DI MASA PANDEMI COVID-19 PADA MATA KULIAH ANIMASI GRAFIS DI PRODI FILM DAN TELEVISI ISI SURAKARTA - Dedi Eko Nurcahyo (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
This research aims to create electronic modules (e-modules) which can later be used as a guide for students to be able to study animation theory and follow practical instructions that can be done independently through e-modules and also to determine the effectiveness of using e-modules used in learning Graphic Animation courses at the Film and Television Study Program ISI Surakarta. The method used is the method of developing a product with the Sadiman model developed in 2009. The research data shows that from the results of student questionnaires, the score for the content feasibility aspect gets a score of 90%, the linguistic aspect gets a score of 85%, the serving aspect gets a score of 83%. All three fall into the very appropriate category. Graphic aspect gets a score of 76% or in the appropriate category. The last is from the aspect of the task getting a score of 82% or in the very appropriate category. The results from media experts show that the feasibility of content, language, presentation, graphics and aspects of the task gets a score of 80% or falls into the very appropriate category. From the results of the questionnaire, it can be concluded that this graphic animation e-module is suitable for use in graphic animation lectures.